2017
DOI: 10.1177/0886260517741627
|View full text |Cite
|
Sign up to set email alerts
|

Cycle of Violence in Schools: Longitudinal Reciprocal Relationship Between Student’s Aggression and Teacher’s Use of Corporal Punishment

Abstract: The purpose of this study is to examine the longitudinal reciprocal relationship between student's aggression and teacher's use of corporal punishment. An autoregressive cross-lagged model was analyzed with the data drawn from 4,051 Korean secondary students (male = 2,084, female = 1,967), in Gyeonggi Education Panel Study for three waves (seventh-ninth grades). Results revealed that student's aggression provoke teacher's use of corporal punishment and also teacher's use of corporal punishment provokes student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Although causal conclusion cannot be drawn from existing evidence, it is reasonable to assume that victimization by teachers in the classroom may expose students as targets of victimization by peers. At the same time, the positive associations between exposure to emotional violence by teachers and students' aggressive behavior as well as perpetration of violence against teachers and peers lend support to the notion of cycles of violence in the classroom (Choi, 2021;Karcher, 2002). Such a cycle may translate beyond school to students' and teachers' use of violence in their families and communities.…”
Section: Correlatesmentioning
confidence: 82%
“…Although causal conclusion cannot be drawn from existing evidence, it is reasonable to assume that victimization by teachers in the classroom may expose students as targets of victimization by peers. At the same time, the positive associations between exposure to emotional violence by teachers and students' aggressive behavior as well as perpetration of violence against teachers and peers lend support to the notion of cycles of violence in the classroom (Choi, 2021;Karcher, 2002). Such a cycle may translate beyond school to students' and teachers' use of violence in their families and communities.…”
Section: Correlatesmentioning
confidence: 82%
“…Studies conducted on physical violence indicated that people, who were angry a lot and did violent behaviors, put a lot of pressure on their bodies, leading to prolonged problems in heart and the nervous system ( Payne and Gottfredson, 2019 ). According to previous studies, aggressive students with no academic achievement provoke their teachers to act violently against them ( Choi, 2021 ). Violence is mostly verbal and occurs frequently in schools with ethnic minorities from marginalized areas ( López García et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found, additionally, that children and educators in Vanuatu, the Solomon Islands and Kiribati supported the use of physical punishment by teachers and saw it as a part of the education and disciplinary processes. Choi (2017) found that the use of the corporal punishments in the name of discipline in Korea does not control the children's behaviour. Choi said that the use of this practice leads to more misbehaviour by children, which in turn leads to more use of corporal punishments by educators against children.…”
mentioning
confidence: 99%